Does flood protection affect urban expansion in the coastal flood-prone area of China? - Wu, Yijing; Li, Jingwei; Wang, Dan; Li, Ling; Shao, Wendi; Du, Shiqiang (Frontiers in Earth Science, 2022)
Understanding the characteristics of urbanization under different flood protection levels is vital for sustainable development in coastal flood-prone areas (CFAs). However, little is known about the potential divergences of coastal urbanization across different flood protection levels in the CFAs of China. To fill this research gap, this study investigated the spatio-temporal changes of urban land expansion in Chinese CFAs and explored their relationships with flood protection levels during 2000–2020. It was found that in 2020, the urban lands accounted for 16.35% of the CFAs, 1.81 times that of the non-CFAs (9.04%). The urban lands increased rapidly in the CFAs across all flood protection levels, with an average annual change rate of 6.51%, which was 2.17 times that of non-CFAs (3.00%) and 3.68 times that of the exposed population growth rate (1.77%). Particularly in counties with low flood protection levels (<50 years), the urban lands expanded by 9.40% annually, 1.44 times that of the whole CFAs; moreover, a large portion (39.58%) of the new urban lands were reclaimed from sea waters. These findings suggest that special attention should be paid to coastal landscape changes in the areas of low flood protection levels to reduce flood risk and ensure sustainable cities and communities. Flood adaptation strategies should be applied to include conserving the coastal ecosystem.